“THE SMILE SQUAD” VIDEO TO IMPROVE STUDENTS’ LISTENING SKILLS AT THE ELEVENTH GRADE OF SMAN 4 BANGKALAN - Safira Husniyah; Mariyatul Kiptiyah; Moh. Arief Wahyudi (Universitas Madura, 2023)
The research aimed at improving the listening skill of The Eleventh Grade Students of SMAN 4 Bangkalan by using “Smile Squad videos” as learning media. It aimed to find and implement some actions to improve the listening skills. The research method was collaborative classroom action research, which was a dynamic and complementary process that included four important steps: planning, implementation, observation, and reflection. The researcher and teacher collaborated together to identify hurdles and weaknesses in the listening learning process, identify certain issues, and plan and implement the proposed measures. The first cycle's findings showed that students' listening skills increased as a result of extensive listening exercise. It was also discovered that watching the “Smile Squads videos” more frequently can help them improve their English. Students steadily improve their ability to detect more spoken English words, distinguish the similar pronunced words and find information from a conversation. The indicators of the success of the implementation were: (1) the students were more enthusiastic in doing listening activities; and (2) the students’ listening skill was improved. Furthermore, the findings were also supported by the means of the students’ listening score which improved from 58 in the preliminary study test to 80 in the cycle test.